2013
DOI: 10.1152/japplphysiol.00372.2013
|View full text |Cite
|
Sign up to set email alerts
|

Beetroot juice and exercise: pharmacodynamic and dose-response relationships

Abstract: Ϫ ] increased in a dose-dependent manner, with the peak changes occurring at approximately 2-3 h. Compared with PL, 70 ml BR did not alter the physiological responses to exercise. However, 140 and 280 ml BR reduced the steady-state oxygen (O2) uptake during moderateintensity exercise by 1.7% (P ϭ 0.06) and 3.0% (P Ͻ 0.05), whereas time-to-task failure was extended by 14% and 12% (both P Ͻ 0.05), respectively, compared with PL. The results indicate that whereas plasma [NO 2 Ϫ ] and the O2 cost of moderate-inten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

61
449
20
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 420 publications
(563 citation statements)
references
References 43 publications
(148 reference statements)
61
449
20
4
Order By: Relevance
“…Consistent with previous investigations, plasma nitrate and nitrite, and exhaled NO concentrations were significantly elevated following dietary nitrate supplementation [1,2,5,8,55,22,39,38], signifying an increase in the 'substrates' available for NO generation via the nitrate-nitrite-NO pathway [11]. Peak plasma nitrite concentration was 602 % higher in BRJ versus PLA, similar to Arnold et al [38] (775 %) (~ 7 mmol nitrate), but considerably greater than reported by Muggeridge et al [22] (134 %) (~ 5 mmol nitrate) and Vanhatalo et al [8] (150 %) (~ 9.3 mmol).…”
Section: Plasma Nitrate Nitrite and Exhaled Nosupporting
confidence: 90%
See 1 more Smart Citation
“…Consistent with previous investigations, plasma nitrate and nitrite, and exhaled NO concentrations were significantly elevated following dietary nitrate supplementation [1,2,5,8,55,22,39,38], signifying an increase in the 'substrates' available for NO generation via the nitrate-nitrite-NO pathway [11]. Peak plasma nitrite concentration was 602 % higher in BRJ versus PLA, similar to Arnold et al [38] (775 %) (~ 7 mmol nitrate), but considerably greater than reported by Muggeridge et al [22] (134 %) (~ 5 mmol nitrate) and Vanhatalo et al [8] (150 %) (~ 9.3 mmol).…”
Section: Plasma Nitrate Nitrite and Exhaled Nosupporting
confidence: 90%
“…Finally, there is some evidence of a dose-response to nitrate supplementation [55,65,66], and it is possible that well-trained athletes may require a high nitrate dose to appreciably alter plasma nitrite concentration relative to untrained individuals [30]. Therefore, the high nitrate dose administered in this study relative to investigations which have not observed an effect of nitrate supplementation (~ 5 -7 mmol) [38][39][40] may have also contributed towards the consistent ergogenic effect observed here.…”
Section: Effect Of Nitrate Supplementation On Running Performance In mentioning
confidence: 49%
“…Taken together, these findings suggest that watermelon juice supplementation might represent an effective nutritional intervention to increase nitric oxide production and bioavailability. deproteinised plasma) used in this study [43]. Therefore, the increase in nitric oxide synthesis after watermelon juice supplementation in this study was likely insufficient to evoke an improvement in cycling economy.…”
Section: Discussionmentioning
confidence: 89%
“…Specifically, they were asked to record food and drink intake for 5 days, starting two days prior to the first control trial and ending on the day of the final control trial. They were provided with a list of foods rich in nitrate and asked to avoid these foods whilst completing the food diary to avoid a potential confounding influence of dietary nitrate intake on the physiological and performance measurements completed in this study [43]. Subjects were instructed to replicate their diet for the final 5 days of the subsequent supplementation periods.…”
Section: Experimental Designmentioning
confidence: 99%
See 1 more Smart Citation